A high gain and high linearity current‐reused CMOS LNA using modified derivative superposition technique with bulk‐bias control. Issue 10 (October 2014) - Dai, Ruofan; Zheng, Yunlong; Zhu, Hongwei; Kong, Weiran; Zou, Shichang
ABSTRACT This article presents the design of a 2.4 GHz low power high gain and high linearity current‐reused CMOS low noise amplifier (LNA) using modified derivative superposition (MDS) technique with bulk‐bias control. The MDS technique with bulk‐bias control is used to extend the auxiliary transistor's bias control range and enhance the linearity performance. The current‐reused topology is utilized to fulfill the low power consumption and high gain, simultaneously. The proposed LNA is fabricated in a 0.18‐μm 1P6M SiGe BiCMOS process and consumes a 6.53 mA quiescent current from a 1 V voltage supply. The measurement results show that the proposed LNA achieves a 24.1 dB power gain, 1.7 dB NF, −18 dB input P1dB, 8.75 dBm IIP3, 13.9 and 19.5 dB input and output return loss, respectively. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2444–2446, 2014